INFLUENCE OF SWIMMING TIME IN SOME PHASES ON FINAL RESULT IN 50M DISCIPLINES - Goran Dimitrić; Maja Batez; Milan Cvetković; Milan Pantović; Marko Jadranski (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2012)
It is possible to analyse swimming results from more aspects. One of the common analysis is how swimming time in some, standardised sectors affects on final result. During swimming in 50m swimming disciplines in short course pools (25meters), lenght of the pool is divided in followed sectors: surface breakpoint positions & times after start, start time 15m, split time 20m, surface breakpoint positions & times after turn, split time 35m, split time 35m, split time 35m and final time. Confirming, affects of swimming time in some sectors on final result, it is possible to find difference bettwen good and bad swimmers. This analyse was managed on swimming results from European short course swimming championships - Szczecin 2011, Poland.